2021
DOI: 10.1186/s40494-021-00576-3
|View full text |Cite
|
Sign up to set email alerts
|

Rationality in pier geometry of Kintaikyo Bridge from viewpoint of river engineering

Abstract: The Kintaikyo Bridge, with its elegant wooden arches, has a unique pier shape and continues to be loved by residents and visitors alike. Although this bridge is an active footbridge and an important landscape element along with the Nishikigawa River and its river beach, the rationality or irrationality of the shape of its piers remains unknown. This paper is intended to clarify the river engineering characteristics of the piers for the first time by conducting 1/129 scale hydraulic model experiments. The shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Classic hydraulic model experiments have been conducted on single piers with simple structural geometries. Cylindrical 2 , 3 , typical rectangular 4 , 5 , and specific bridge-pier geometries 6 have been examined. Jain et al 7 conducted experiments on the mixtures of riverbed materials at pier installation sites.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Classic hydraulic model experiments have been conducted on single piers with simple structural geometries. Cylindrical 2 , 3 , typical rectangular 4 , 5 , and specific bridge-pier geometries 6 have been examined. Jain et al 7 conducted experiments on the mixtures of riverbed materials at pier installation sites.…”
Section: Introductionmentioning
confidence: 99%
“…Through experiments on a thick rectangular pier, Kadono et al 20 showed that the scour area is enlarged when skew is toward the river flow, considering the collapse of a railroad bridge. Sato 6 experimentally investigated the effect of a skewed spindle shape on the scour and water level changes. Fael et al 21 tested rectangular and several other pier geometries, including group piles, and discussed the equilibrium scour depth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations